Corporate Tax Cuts for Small Firms: What Do Firms Do? - Wei Cui; Mengying Wei; Weisi Xie; Jing Xing (Center for Economic Studies and ifo Institute (CESifo), 2021)
What do small firms do when given an income tax cut? We address this question by examining the consequences of a sharp reduction in the corporate income tax rate for small- and micro-profit enterprises (SMPE) in China based on confidential tax returns. Utilizing the gradual increases in the qualifying threshold for SMPEs during 2010-2016, we find that newly qualified SMPEs with positive taxable income increased investment, interest expense and productivity. SMPEs in taxable losses did not respond to the tax cut. The tax cut induced more SMPEs to register, especially those in financially constrained sectors. Despite these positive effects, firms' fixed asset growth slows down when they get closer to the SMPE threshold. Our study contributes to understanding the effect of tax preferences for small businesses.
Keywords: 330; tax incentives; small firms; productivity; investment; firm entry